Nurse‐led vascular risk assessment in a regional Victorian Indigenous primary care diabetes clinic: An integrated Diabetes Education and Eye disease Screening [iDEES] study. (20th April 2022) - Atkinson‐Briggs, Sharon; Ryan, Christopher; Keech, Anthony; Jenkins, Alicia; Brazionis, Laima; ,
Abstract: Aim: The aim was to describe vascular risk factors in Australian adults with diabetes attending an Indigenous primary care nurse‐led diabetes clinic. Design: This was a cross‐sectional descriptive single‐site study. Methods: Vascular risk factor data were extracted from the electronic health records of participants in the nurse‐led integrated Diabetes Education and Eye disease Screening (iDEES) study at a regional Victorian Indigenous primary health‐care clinic between January 2018 and March 2020. Results: Of 172 eligible adults, 135 (79%) provided data. Median (IQR) age was 56 (46–67) years; 89% were Indigenous; 95% had Type 2 diabetes of median (IQR) duration of 6 (2–12) years and 48 (36%) were male. Median HbA1c, blood pressure, cholesterol (total; LDL and HDL), triglycerides, eGFR, CRP and BMI were 8.0% (64 mmol/mol), 127/78 mm Hg, 4.2; 1.9; 1.1 mmol/L, 2.3 mmol/L, 89 ml/min/1.73 m 2, 7.0 mg/L and 32.4 kg/m 2 . Of nine clinical risk factors, the median (IQR) number of risk factors at target was 4 (3–5) for women and 3 (2–5) for men, p χ 2 = 0.563. Clinical targets for BMI, HbA1c, blood pressure, triglycerides, total cholesterol, LDL cholesterol, urine albumin: creatinine ratio, HDL cholesterol and smoking were met by 14%, 34%, 38%, 39%, 44%, 52%, 54%, 62% and 64%, respectively. Conclusion: A nurse‐led model of integrated clinical risk factor assessment and diabetes education identified suboptimal levels of clinical risk factor control for avoiding diabetes chronic complications amongst Australian adults with diabetes in an Indigenous primary care setting. Impact: A nurse‐led model of diabetes care integrating clinical risk factor assessment into a diabetes education service is achievable. Understanding by stakeholders, including people with diabetes, their clinicians and health services, of the importance of regular monitoring of risk factors impacting diabetes complications is important. The novel nurse‐managed iDEES primary‐care model of care can assist. Trial registration: This study was registered with the Australian New Zealand Clinical Trials Registry (ACTRN12618001204235).